The Journal of Visualization and Interaction: A diamond open-access journal for the InfoVis and HCI communities. - Besançon, Lonni; Echtler, Florian; Kay, Matthew; Wacharamanotham, Chatchavan (Journal of Visualization and Interaction, 2023)
The Journal of Visualization and Interaction (JoVI) is a venue for publishing scholarly work related to the fields of visualization and human-computer interaction. Contributions to the journal include research in: • how people understand and interact with information and technology, • innovations in interaction techniques, interactive systems, or tools, • systematic literature reviews, • replication studies or reinterpretations of existing work, • and commentary on existing publications. Cross-disciplinary work from other fields such as statistics or psychology, which is relevant to the fields of visualization or human-computer interaction is also welcome.